A framework for using the concept of urban resilience in responding to climate-related disasters. Issue 4 (8th August 2022) - Torabi, Elnaz; Dedekorkut-Howes, Aysin; Howes, Michael
ABSTRACT: Resilience is an important concept in planning/policy. The diversity of theoretical conceptualisations, lack of a clear definition, and ambiguity in application to cities have made urban resilience a difficult concept to pin-down. This paper explores the dimensions of urban resilience to conceptualise and operationalise resilience, connecting theory and practice using two Australian cases. The findings call for a reconsideration of the existing dimensions (infrastructural, ecological, social and community, economic, and institutional) and highlight urban political resilience, a new dimension essential for a transformative adaptation approach.